2010
DOI: 10.1007/s11746-010-1564-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Authentication of Significant Chinese Edible Oilseed Oils by Stable Carbon Isotope Analysis

Abstract: The ratios of stable carbon isotopes (d 13 C) of 12 oils extracted from Chinese edible oilseed samples and their individual fatty acids were determined by elemental analysis-isotope ratio mass spectrometry (EA-IRMS) and gas chromatography-isotope ratio mass spectrometry (GC-IRMS). The results have demonstrated that the d 13 C ratios of the oils from C3-plant seeds range from -26.8 to -30.7%, while the d 13 C ratios of C4-plant maize oil are in the interval of -14.1 to -16.2%. Eighteen fatty acids were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…As walnuts show high fat contents (50-70%) 1 we compared our bulk 13 C-values (‰) with those from walnut oils, which were in good accordance. 54,55 With lipids being the most depleted organic components occurring in natural products, 26 the fat content can have an impact on the 13 C-value (‰) of plant material. Indeed, it was reported that in plant material high lipid contents affected bulk 13 C-values (‰).…”
Section: C-values (‰) Of German Walnutsmentioning
confidence: 99%
“…As walnuts show high fat contents (50-70%) 1 we compared our bulk 13 C-values (‰) with those from walnut oils, which were in good accordance. 54,55 With lipids being the most depleted organic components occurring in natural products, 26 the fat content can have an impact on the 13 C-value (‰) of plant material. Indeed, it was reported that in plant material high lipid contents affected bulk 13 C-values (‰).…”
Section: C-values (‰) Of German Walnutsmentioning
confidence: 99%
“…Many Asian researchers have investigated the compositions of FAs, triacylglycerols, sterols, tocopherols, phenolic compounds, volatiles, and carbon stable isotopes in perilla oils from Korea, China, India, and Thailand. Only one published study examined the patterns of carbon stable isotope ratio and FA composition of Chinese perilla oil added with corn or soybean oil . However, to the best of our knowledge, no published studies have authenticated perilla oil by analyzing the chemical constituents in the oil.…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Camellia oil (CO) is obtained from Camellia oleifera seeds, is characterized by the high proportion of oleic acid (74-89%) [5]. CO has been used as a cooking oil in China for 2300 years [9].…”
Section: Introductionmentioning
confidence: 99%